Investigation of flow and flame propagation in a spark ignition direct injection engine using particle image velocimetry - Shen, L; Willman, C; Stone, R (American Society of Mechanical Engineers, 2022)
Variations in the in-cylinder flow before and during combustion influence the propagation of the flame in spark ignition direct injection (SIDI) engines, which leads to variations in combustion between engine cycles. Accommodating such cycle-to-cycle variation in production engines requires design compromises that may reduce efficiency. The in-cylinder flow and flame evolve rapidly during combustion, and due to the existence of cyclic variation, the flame propagation in individual cycles cannot be replicated by taking measurements at different timings over different cycles, hence crank-angle-resolved measurements in the same cycle are needed. However, such high-speed flow and flame measurements usually require combining multiple laser-based diagnostic techniques, which can be costly due to the need for multiple lasers with high repetition rates at different wavelengths. In this work, the crank-angle-resolved flow velocity and the flame propagation on a swirl plane in an optically accessible SIDI engine were simultaneously measured by a single laser-based diagnostic technique – high-speed planar particle image velocimetry (PIV). In-plane flame boundaries were inferred from the absence of PIV seeding oil droplets in the burned gas regions. Line-of-sight flame images from two orthogonal views were recorded synchronously with the PIV data in order to validate the in-plane flame boundaries derived from the PIV data. The impact of the neighbouring flow on the evolution of the flame boundaries over crank angles is examined.